HUBUNGAN KEMAMPUAN MEMBUAT PETA KONSEP (CONCEPT MAPPING) DENGAN HASIL BELAJAR BIOLOGI SISWA PADA SUB MATERI KLASIFIKASI MAKHLUK HIDUP KELAS X SMA SWASTA ESA PRAKARSA SELESAI KABUPATEN LANGKAT - Siti Lestari; Herkules Abdullah; Mudjio Mudjio (Jurnal Pelita Pendidikan, 2016)
This study aimed to determine the correlation of students ability to make concept maps with student learning outcomes biology class X IPA1 SMA Swasta Esa Prakarsa Selesai district Langkat Tp. 2016/2017. The population in this study was all students of class X SMA Swasta Esa Prakarsa Selesai district Langkat Tp. 2016/2017. While the study sample taken at random sampling of the class X IPA1 amounted to 38 people. The method used in this research is descriptive. From the results of data analysis and hypothesis testing there were some things that the findings in this study; Average students' ability to make a concept map is 77.08 while the student learning outcomes in sub material classification of living things have an average of 71.23. Hypothesis test results tcount > ttable: 15.08 > 1.6775  meant that in this study the Ha was accepted and Ho was rejected which meant that there were significant correlation between the ability to make concept map with student learning outcomes. Based on a test of the determination of the coefficient obtained contribution concept map of 86.49%.Keyword: Concept Mapping, Learning Outcomes, The Classification of Living